Enhanced Action Potential Passage Through the Node of Ranvier of Myelinated Axons via Proton Hopping - Kier, Lemont; Hall, Lowell; M. Tombes, Robert (Current Computer - Aided Drug Design, 2015)
Nerve impulses travel along myelinated axons as much as 300-fold faster than they do along unmyelinated axons. Myelination is essential for normal nervous system behavior in vertebrates as illustrated by leukodystrophies, such as amyotrophic lateral sclerosis (ALS) or multiple sclerosis (MS), where myelin is degenerated or damaged. The increased conduction velocity that occurs in myelinated axons is dependent on gaps in the myelin called Nodes of Ranvier that are enriched in ion channels. These Nodes are separated by long stretches of myelin insulation where no transmembrane ion conductance occurs. It is believed that the action potential jumps or skips between nodes, conserving its information content, while maintaining its speed. In this study, a model is presented that implicates Nodes of Ranvier as responsible for regenerating the proton hopping that is responsible for nerve impulse conductance in myelinated axons.
Keywords: node of Ranvier